Large Eddy Simulation of Premixed Stratified Swirling Flame Using the Finite Rate Chemistry Approach - Yinli Xiao; Zhengxin Lai; Wenyan Song (International Journal of Aerospace Engineering)
Large eddy simulations of a stratified swirling flow of a Cambridge swirl burner for both nonreacting and reacting cases are conducted using a finite rate chemistry approach represented by a partially stirred reactor model. The large eddy simulation predictions are compared with experimental measurements for velocity, temperature, and concentrations of major species. The agreement is found in overall trend of velocity prediction, but temperature and concentration of major species show slight discrepancies in the central region. Two reduced chemical mechanisms are examined in the present paper with the objective of assessing their capabilities in predicting swirling flame characteristics, and the distinct difference using two mechanisms is found in CO distribution profiles, which is considered the consequence of different kinetics of CO-CO2 equilibrium. Flow structures are qualitatively and quantitatively analyzed with numerical results. Large-scale vortex structures and precession motions are observed in both nonreacting and reacting cases. Frequency of vortex shedding is identified from the point data of instantaneous velocity in the discharging stream-induced shear layer. On this basis, the intensity and frequency of precession motion are shown to be enhanced in the presence of combustion. Large-scale wrinkling of the flame surface is resolved and characterized in the flame zone, and the effect of mixture stratification is then further discussed.